Rural radio training in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Since its inception CTA has always recognized the importance of radio as an information medium in ACP countries where illiteracy is high and the press often weak or unreliable. CTA has therefore forged special links with the presenters, producers...